Sistemas de seguridad y salud en el trabajo, entre los países miembros de la comunidad andina de naciones - González Zaruma, Mónica Gianella (2023)
Over the years, the regulations referring to occupational health and safety systems have evolved, since different work modalities have appeared, however, the management of the possible factors that put people at risk in the workplace. The prevention of risks that may arise as a consequence of this, which generates a sequel that negatively impacts the well-being of workers, directly affecting the health and well-being of the working population of the member countries of the Andean Community of Nations. In this context, it is evident that, despite each member nation, has a regulation related to safety and health at work, it is distinguished that there is little reference to a decadent relevance to compliance with it within each country. Therefore, it was necessary to develop a study with the purpose of carrying out a comparative analysis of occupational health and safety regulations, among the member countries of the Andean Community of Nations. The applied methodology included the design of a proactive, explanatory and descriptive-comparative investigation, applying the qualitative method and the sampling technique, through which the member countries of the Andean Community of Nations were selected: Colombia, Ecuador, Peru and Bolivia. The results obtained revealed that the Colombian regulations are the most complete in terms of guaranteeing an efficient system to promote safety and health at work, compared to other countries. It is concluded that it is necessary to implement the proposal developed in the case of Ecuador to guarantee the greatest safety and health at work in cooperation with the Andean Community of Nations. Keywords: safety, occupational risk, occupational health, occupational disease, accidents at work